Dinamika Kelekatan, Pola Asuh, Konsep Diri dan Teman Sebaya Terhadap Perilaku Agresif (Studi Kasus Perilaku Seorang Anak Agresif Pemarah Usia 10 Tahun di Sekolah XYZ) - Moyana Modesta Sebayang (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
Aggressive behavior in children is characterized by deliberate actions intended to harm others physically or psychologically. Understanding the development of such behavior is crucial in the school environment, as it affects children’s learning and social interactions. This study aims to examine the case of a child who exhibited aggressive behavior by exploring family factors, parenting style, self-concept, and peer influence. This qualitative research employed a case study approach and was conducted at an elementary school in West Jakarta from April to October 2013. The subject was a 10-year-old boy in the fourth grade, the eldest of two siblings of Chinese-Indonesian descent. Data were collected through interviews, observations, and document analysis, and validated using triangulation. The findings revealed that the child’s secure attachment changed due to negative family conditions, particularly harsh discipline and reduced maternal attention after the birth of a younger sibling. The authoritarian parenting style, which emphasizes high standards and strict discipline, triggered aggressive behavior. A lack of positive reinforcement and constant comparisons with others fostered a negative self-concept. In addition, peer influence—especially exposure to verbal aggression—intensified the child’s emotional outbursts, particularly during group activities such as sports. In conclusion, children’s aggressive behavior is influenced by interrelated factors, namely insecure attachment, authoritarian parenting, a weak self-concept, and peer influence. Addressing these issues requires consistent parental support, positive reinforcement, and the role of educators in helping children regulate emotions and build healthy social interactions.